Spraying equipment for crop protection Part 5. Specification for tank nominal volume and filling hole diameter (BSI, 1992)
Crop protection, Agronomy, Agriculture, Agricultural equipment, Spraying equipment (agriculture), Tanks (containers), Volume, Filling devices, Diameter, Liquid-level indicators, Graduations